Treatment of newly diagnosed sarcoid-associated pulmonary hypertension with ambrisentan and tadalafil combination therapy - Abston, Eric; Hon, Stephanie; Lawrence, Romy; Berman, Jeffrey; Govender, Praveen; Farber, Harrison W. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Sarcoid Associated Pulmonary Hypertension (SAPH) is a common complication of sarcoidosis and is associated with poor prognosis. SAPH can be due to multiple synergistic mechanisms and current therapeutic strategies treat systemic sarcoidosis and pulmonary hypertension separately. Several studies have been performed to develop an effective therapy for SAPH but have been met with mixed results. The AMBITION trial successfully treated incident patients with pulmonary arterial hypertension (PAH) with the upfront combination of ambrisentan and tadalafil; however combination therapy has not yet been studied in patients with SAPH. Here we report a cohort of patients with newly diagnosed SAPH who were treated with upfront combination therapy per the AMBITION study protocol. We report three subjects with newly diagnosed SAPH who were treated with combination ambrisentan and tadalafil. Baseline hemodynamics were compared with those from surveillance right heart catheterization while on therapy. Mean follow up period was 17 months. Each subject demonstrated clinical and hemodynamic improvement with combination therapy. This series is the first to evaluate upfront combination ambrisentan and tadalafil therapy for treatment of newly diagnosed SAPH. Despite the impressive clinical and hemodynamic improvement, the study is limited by its small size and retrospective nature. While these initial results are promising, further work is needed to fully evaluate this regimen for treatment of SAPH.